Исследование взаимосвязи абразивной способности микропорошков синтетического алмаза и шероховатости обработанной поверхности с зерновым составом и средним размером зерен фракций - Петасюк, Г.А.; Никитин, Ю.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Experimental research of effect of grain composition indices of synthetic diamond micron powders on abrasive ability of the powders and roughness of finished surface has been carried out. Empirical mathematical models of correlation between abrasive ability and roughness of finished surface and grain composition indices as well as average grit size of fractions have been developed.